Analisis Political Branding Calon Kepala Daerah dalam Pilkada Aceh 2017 - Asmaul Husna (Jurnal Komunikasi Global, 2017)
February 15th, 2017, Aceh held the election for the third times. 3,443,583 voters spread across 23 districts/cities contested by six pairs of candidates either through individual or political parties. Throughout the history of democratic elections in Aceh, the 2017 election was the greatest battle for the ideological heirs of Hasan Tiro after GAM has been involved in politics. Four out of six candidates are known as former prominent figures of Aceh Free Movement (GAM) who can be classified into two categories, former combatants and non-combatants. The political competition tension requires the candidates to create the most effective tactics in the effort to gain the votes. Using the concept of political branding developed by Gelder, Sonies, and Mensah, this research aims to reveal the extent to which the social background differences of contestants influence the political branding presented during the 2017 Aceh Election campaign. From the analysis of verbal, visual, and vocal objects that were scattered and documented in various contestant’s official campaign channels, it is found that the different social backgrounds of these contestants have brought differences in self-identification, political products, and positioning in their political branding.